Opening the Schrödinger Box: Short- and Long-Range Mammalian Heart Rate Variability - Weiser-Bitoun, Ido; Davoodi, Moran; Rosenberg, Aviv A.; Alexandrovich, Alexandra; Yaniv, Yael (Frontiers in Physiology, 2021)
(e.g. endocrine) and internal pacemaker mechanisms govern short (milliseconds-seconds)- and long (seconds-minutes)-range heart rate variability (HRV). However, there is a debate regarding the identity of the mechanism underlying HRV on each time scale. We aim to design a general method that accurately differentiates between the relative contribution of the ANS and pacemaker mechanisms to HRV in various mammals, without the need for drug perturbations or organ isolation. Additionally, we aim to explore the universality of the relative contribution of the ANS and pacemaker system of different mammals. Methods: This work explored short- and long-range HRVs using published ECG data from dogs, rabbits and mice. To isolate the effects of ANS on HRV, ECG segments recorded before and after ANS-blockade were compared. Results: Differentiation of the ANS from extrinsic and intrinsic pacemaker mechanisms was successfully achieved. In dogs, the internal pacemaker mechanisms were the main contributors to long-range and the ANS to short-range HRV. In rabbits and mice, the ANS and the internal pacemaker mechanisms affected both time scales and anesthesia changed the relative contribution of the pacemaker mechanism to short- and long-range HRVs. In mice, the extrinsic mechanisms affected long-range HRV, while their effect was negligible in rabbits. Conclusions: We offer a novel approach to determine the relative contributions of ANS and extrinsic and intrinsic pacemaker mechanisms to HRV and highlight the importance of selecting mammalian research models with HRV mechanisms representative of the target species of interest.